REVIEW: FORMULASI TABLET EFFERVESCENT BERBAHAN DASAR ALAMI - Ayu Aprilia; Nur Imam Satria; Ade Dwi Setyarini; Maherawati Maherawati (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Natural ingredients are the people's choice and are a healthy lifestyle in consuming food. One of the servings of functional drinks from natural ingredients is by effervescent tablets. The most natural ingredients used as the main ingredients of effervescent tablets are fruits, rhizomes, rind, leaves, and seeds. The most active compounds found in effervescent tablets from natural ingredients are antioxidant compounds (phenolic, flavonoids, tannins, saponins, and anthocyanins), vitamins (A, B1, B2, C, and D), and minerals (potassium, sodium, iron, and magnesium). The method most widely used to produce effervescent tablets is the wet granulation method. Other methods used are the dry granulation method and direct compression. The formulation of effervescent tablets consists of acid, base, binder, lubricant, filler, and sweetener components. The most widely used formulations of natural effervescent tablets are citric acid, sodium bicarbonate as a base, polyvinyl polydone (PVP) as a binder, PEG 6000 as a lubricant, lactose as a filler, and aspartic acid as a sweetener. The production of effervescent tablets from natural ingredients is the development of ways to consume functional drinks that are more practical and beneficial to health.